2021
DOI: 10.1371/journal.pgph.0000083
|View full text |Cite
|
Sign up to set email alerts
|

Corona virus fear among health workers during the early phase of pandemic response in Nepal: A web-based cross-sectional study

Abstract: Health workers involved in the COVID-19 response might be at risk of developing fear and psychological distress. The study aimed to identify factors associated with COVID-19 fear among health workers in Nepal during the early phase of the pandemic. A web-based survey was conducted in April-May 2020 among 475 health workers directly involved in COVID-19 management. The Fear Scale of COVID 19 (FCV-19S) was used to measure the status of fear. Multivariable logistic regression was performed to identify factors ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
(40 reference statements)
2
13
0
Order By: Relevance
“…Fear and apprehension due to COVID-19 had an impact on their daily living, social interaction, and psychological well-being and echoes with the existing literature [23][24][25]. Fear surrounding COVID-19 was associated with their vulnerability due to the highly contagious nature of the disease, lack of medicine, and (full doses) of vaccines, and such fears, and stigma were higher among the health workers [8,26]. Undoubtedly, fears were further exacerbated by the shared anecdotes from their peers, neighbours and family members, how they journeyed through disease including the loss of loved ones [27].…”
Section: Experience Perceptions and Impacts Related To Covid-19supporting
confidence: 55%
“…Fear and apprehension due to COVID-19 had an impact on their daily living, social interaction, and psychological well-being and echoes with the existing literature [23][24][25]. Fear surrounding COVID-19 was associated with their vulnerability due to the highly contagious nature of the disease, lack of medicine, and (full doses) of vaccines, and such fears, and stigma were higher among the health workers [8,26]. Undoubtedly, fears were further exacerbated by the shared anecdotes from their peers, neighbours and family members, how they journeyed through disease including the loss of loved ones [27].…”
Section: Experience Perceptions and Impacts Related To Covid-19supporting
confidence: 55%
“…Aside from psychological distress, our research will aid in identifying possible indicators of social support and stigma that may impact the physical and mental health of Nepali health care workers. Previous studies conducted in Nepal did not look into stigma, social support, and stress despite the many studies in Nepal included mental health outcomes and fears [3,12,20]. There is scant information about stigma and social support relating to stress, which could be an interesting outcome to look at in low and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…As this pandemic has intensified, with rising cases and deaths globally, so too have feelings of worry and fear in response to ongoing COVID-19 community transmission [ 1 , 2 ]. Studies from across the world have demonstrated that many workers are afraid of contracting and transmitting COVID-19 while at work [ 3 , 4 , 5 , 6 ]. Fear is an adaptive defense mechanism for humans when confronted with a risk or danger, however chronic fear can lead to adverse mental health outcomes and behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…A Canadian study from May 2020 reported that mental health has worsened since the onset of the COVID-19 pandemic, due in large part to economic uncertainty and fear of illness [ 7 ]. Notably, these negative mental health effects have largely been observed in work settings that are predominantly public-facing and more exposed to viral transmission [ 3 , 4 , 5 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%